Retrospective 1-year outcome follow-up in 200 patients supported with HeartMate 3 and HeartWare left ventricular assist devices in a single centre. (16th April 2020) - Mueller, Marcus; Hoermandinger, Christoph; Richter, Gregor; Mulzer, Johanna; Tsyganenko, Dmytro; Krabatsch, Thomas; Starck, Christoph; Stein, Julia; Schoenrath, Felix; Falk, Volkmar; Potapov, Evgenij
Abstract: OBJECTIVES: Various trials have assessed the outcome and reliability of the HeartWare HVAD (HW) and HeartMate 3 (HM3) left ventricular assist devices. A direct comparison of clinical outcomes and of the complication profile of these 2 left ventricular assist devices is lacking. We present a retrospective analysis of patients supported with HM3 and HW as a left ventricular assist device. METHODS: Preoperative data, complications and outcomes including a 1-year follow-up of patients supported with the HM3 and HW in a single centre were retrospectively analysed. Both pumps were implanted on- or off-pump, employing standard and minimally invasive techniques. For logistic reasons, the 2 device types were implanted in an alternating manner, thereby reducing the systematic bias for pump selection. We considered this to be an appropriate approach, as no differences in respect of survival or the complication profile of the two device types have been demonstrated. Anticoagulation was similar in patients with both pumps according to our anticoagulation protocol, with a target international normalized ratio of 2.5–3.0, a home monitoring system and blood pressure management with a mean arterial target pressure of 70–80 mmHg. RESULTS: Between October 2015 and April 2017, 100 patients underwent implantation of the HW and 100 patients underwent implantation of the HM3. The median time on the device was 0.98 years (range 0–2.23 years). The median age was 58.5 (51–65) versus 57 (49–64) years ( P  = 0.456); the number of male patients was 87 versus 88 ( P  = 0.831). Of the HW patients, 73% were rated as having an INTERMACS level I or II, compared to 57% of the HM3 patients ( P  = 0.018). There were no further differences in preoperative data. A total of 14 patients had pre-, intra- or post-pump blood flow obstruction in the HW group versus 4 in the HM3 group [hazard ratio (HR) 2.5 (0.7–8.8), P  = 0.103]. There were no differences regarding gastrointestinal bleeding [HR 1.25 (0.56–2.64), P  = 0.624] or driveline infection (0.68 vs 0.8 events per patient-year, P  = 0.0789). The incidence of ischaemic stroke was similar in both groups [HR 0.72 (0.25–2.09), P  = 0.550]. Cerebral bleeding was more frequent in patients supported with HW [HR 6.79 (1.43–32.20), P  = 0.016]. The incidence of cerebrovascular accidents, on the other hand, was similar in both groups [HR 1.85 (0.83–4.19), P  = 0.13]. The incidence of haemocompatibility-related adverse events, however, was significantly higher in the HW group (113 points corresponding to 1.28 events per patient-year versus 69 points corresponding to 0.7 events per patient-year, P  < 0.001). The 1-year survival was similar in both groups [62.2%, 95% confidence interval (CI) (0.53–0.73) vs 66.7%, 95% CI (0.58–0.767), P  = 0.372]. CONCLUSIONS: Our data show that the complication profile differs between the 2 pumps, but that early survival is comparable.